2021
DOI: 10.3390/brainsci11010071
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex Involvement during Dual-Task Stair Climbing in Healthy Older Adults: An fNIRS Study

Abstract: Executive function and motor control deficits adversely affect gait performance with age, but the neural correlates underlying this interaction during stair climbing remains unclear. Twenty older adults (72.7 ± 6.9 years) completed single tasks: standing and responding to a response time task (SC), ascending or descending stairs (SMup, SMdown); and a dual-task: responding while ascending or descending stairs (DTup, DTdown). Prefrontal hemodynamic response changes (∆HbO2, ∆HbR) were examined using functional ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…26,33 However, in healthy older adults, stair ascent and descent may not be associated with different cognitive load. 43 In agreement, a previous work by Gaillardin and Baudry 14 did not report a difference in DTC between ascent and descent.…”
Section: The Impact Of Amci On Dual-task Performance Is More Pronounc...supporting
confidence: 88%
“…26,33 However, in healthy older adults, stair ascent and descent may not be associated with different cognitive load. 43 In agreement, a previous work by Gaillardin and Baudry 14 did not report a difference in DTC between ascent and descent.…”
Section: The Impact Of Amci On Dual-task Performance Is More Pronounc...supporting
confidence: 88%
“…Salzman et al [ 55 ] investigated the neural mechanisms underlying the interactions between gait performance, age, and deficits in executive function and motor control during stair climbing. Their study involved 20 men and women (mean age 73 years) from a community in Canada.…”
Section: Neurophysiological Biomarkersmentioning
confidence: 99%
“…The copyright holder for this this version posted November 11, 2022. ; https://doi.org/10.1101/2022.11.08.22282071 doi: medRxiv preprint in 3 studies (Marusic et al, 2019, St George et al, 2021, Rosso et al, 2017, arm tracking in 1 study (Corp et al, 2018), and stair climbing in 1 study (Salzman et al, 2021a). For dual-task paradigm, cognitive tasks were performed as follows: 19 studies (Chaparro et al, 2017, Chen et al, 2017, George et al, 2019, Hernandez et al, 2016, Hoang et al, 2022, Holtzer et al, 2018, Holtzer et al, 2019a, Holtzer et al, 2019b, Holtzer et al, 2011, Holtzer et al, 2022, Ross et al, 2021, Wagshul et al, 2019, Rosso et al, 2017, Salzman et al, 2021a, Salzman et al, 2021b, Beurskens et al, 2014, Corp et al, 2018, Hernandez et al, 2020, Marusic et al, 2019, Pakray et al, 2021, Stuart et al, 2019, Talamonti et al, 2022, Chen et al, 2022, Hassan et al, 2020, Hawkins et al, 2018) used inhibitory control tasks (i.e., alternate letters of alphabet and auditory choice reaction), 14 studies (Hassan et al, 2020, Hawkins et al, 2018, Hoang et al, 2022, Maidan et al, 2016, Maruya et al, 2021, Mirelman et al, 2017, Teo et al, 2021…”
Section: Study Characteristicsmentioning
confidence: 99%
“…4 studies (Beurskens et al, 2014, Holtzer et al, 2019b, Holtzer et al, 2022 out of the 33 studies (12%) demonstrated an unclear risk in the domain of confounding. 5 studies (15%) showed a high risk of bias in the classification of interventions (Corp et al, 2018, Marusic et al, 2019, Rosso et al, 2017, Salzman et al, 2021a, St George et al, 2021. 2 studies (6%) showed a high risk of bias in selection of the reported results (Rosso et al, 2017, Teo et al, 2021.…”
Section: Risk Of Biasmentioning
confidence: 99%